Mitochondrially produced ATP affects stem cell pluripotency via Actl6a‐mediated histone acetylation. Issue 4 (5th January 2018) - Zhang, Ying; Cui, Peng; Li, Yuhuan; Feng, Guihai; Tong, Man; Guo, Lu; Li, Tianda; Liu, Lei; Li, Wei; Zhou, Qi
Abstract : ATP is mainly generated by glycolysis in pluripotent stem cells (PSCs) and is consumed to maintain cell viability. Differences in mitochondrial activity among induced (i)PSCs with different degrees of pluripotency are poorly understood. In this study, by comparing gene expression and mitochondrial activity among iPSCs with different degrees of pluripotency, we found that mitochondrial complex I gene expression, complex I activity, and cellular ATP levels were much higher in fully pluripotent stem cell lines than in partially pluripotent stem cell lines. Actin‐like protein 6a (Actl6a), a component of ATP‐dependent chromatin remodeling and histone acetylation complexes, was more highly expressed in fully pluripotent stem cell lines. ATP promoted Actl6a expression and histone acetylation. Actl6a knockdown reduced the pluripotency of embryonic stem cells (ESCs), and this reduction could not be rescued by the addition of ATP. Furthermore, inhibiting ATP formation by treatment with rotenone reduced the pluripotency of ESCs. These data suggest that the abundance of mitochondrially produced ATP affects stem cell pluripotency via Actl6a‐mediated histone acetylation.— Zhang, Y., Cui, P., Li, Y., Feng, G., Tong, M., Guo, L., Li, T., Liu, L., Li, W., Zhou, Q. Mitochondrially produced ATP affects stem cell pluripotency via Actl6a‐mediated histone acetylation. FASEB J. 32, 1891–1902 (2018). www.fasebj.org